Water soluble Ir(III) complexes towards organised phases and nanostructured IrO2 thin films - Scarpelli, Francesca; Carbone, Vincenzo; Godbert, Nicolas (My University, 2018)
This thesis comprises three main macro-topics: water-soluble Iridium (III) complexes, Iridium-based metallogels and nanostructured Iridium Oxide (IrO2). More specifically, the synthesis of new water-soluble cationic Ir(III) complexes has been performed through a simple methodology which involves the incorporation of hydrophilic counterions into the final compounds. Some of the synthesized complexes have shown supramolecular organization in water. These self-assembling architectures have been thoroughly investigated through the combination of complementary characterization techniques, in particular Polarized Optical Microscopy (POM), Transmission Electron Microscopy (TEM), Powder X-Ray Diffraction (PXRD), etc. According to the nature of the featuring ligands, the water-soluble Ir(III) complexes display features of metallogels or lyotropic liquid crystals. The use of these highly organized metallo-hydrogels as Structural Directing Agent (SDA), and concomitantly as direct metal source, has been exploited for the preparation of nanostructured IrO2 powders and thin films. All the presented materials display appealing features for specific applications: water-soluble Ir(III) complexes could represent interesting candidates for anticancer drugs or bioimaging probes, Ir(III) metallogels could find applications in thermosensing or as templating agents, and finally nanostructured IrO2 could be employed in electrochromic devices and catalytic processes.
Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXX
Keywords: Chemistry; Technical; Supramolecular chemistry